Relationship of Telehealth Platform Usage with Mental Health Level in RSUP Dr. Hasan Sadikin Bandung Year 2025 - Suhardono (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
This study examines the impact of telehealth platform use on nurses’ mental health amid shifting work patterns and rising digital demands. Increased workload, adaptation to new technologies, and changes in patient interaction may trigger psychological problems, especially in facilities actively adopting telehealth. A quantitative cross-sectional design was conducted at RSUP Dr. Hasan Sadikin Bandung in 2025. The sample consisted of 75 nurses selected using simple random sampling. Data were collected through structured questionnaires measuring levels of telehealth use and general mental health. Univariate analysis described frequency distributions, while bivariate analysis used the chi-square test with a significance level of 0.05. The univariate results showed that 70.7% of nurses had high telehealth use, and 60% experienced poor mental health conditions. Bivariate analysis indicated a significant relationship between telehealth use and nurses’ mental health (p-value = 0.004). Nurses with high telehealth use had a 2.3 times greater risk of experiencing mental health disorders compared to those with lower use. In conclusion, telehealth platform use significantly affects nurses’ mental health. These findings highlight the importance of digital workload management policies, strengthened institutional support, and continuous promotive and preventive programs to maintain nurses’ mental well-being.